Exploiting the Immunogenic Potential of Cancer Cells for Improved Dendritic Cell Vaccines - Vandenberk, Lien; Belmans, Jochen; Van Woensel, Matthias; Riva, Matteo; Van Gool, Stefaan W. (Frontiers in Immunology, 2016)
Cancer immunotherapy is currently the hottest topic in the oncology field, owing predominantly to the discovery of immune checkpoint blockers. These promising antibodies and their attractive combinatorial features have initiated the revival of other effective immunotherapies like dendritic cell (DC) vaccinations. Although DC-based immunotherapy can induce objective clinical and immunological responses in several tumor types, the immunogenic potential of this monotherapy is still considered suboptimal. Hence, focus should be directed on potentiating its immunogenicity by making step-by-step protocol innovations to obtain next-generation Th1-driving DC vaccines. We review some of the latest developments in the DC vaccination field, with a special emphasis on strategies that are applied to obtain a highly immunogenic tumor cell cargo to load and to activate the DCs. To this end, we discuss the effects of three immunogenic treatment modalities (ultraviolet light, oxidizing treatments and heat shock) and five potent inducers of immunogenic cell death (radiotherapy, shikonin, high-hydrostatic pressure, oncolytic viruses and (hypericin-based) photodynamic therapy) on DC biology and their application in DC-based immunotherapy in preclinical as well as clinical settings.